EDUCATION OF HEIMLICH MANEUVERS IN CHILDREN IN THE GRIEVING MARIA MONASTERY TPA IN OVERCOMING AIRWAY CLOCKIES - Krowa, Yuliana Reginaldis Rosali; Hilpriska Danal, Paskaliana; Roida Eka, Angelina; Xaverius Meku, Fransiskus; Handi, Heribertus (LPPM Univ. Ibn Khaldun Bogor, 2023)
Choking is one of the causes of increased morbidity and mortality in children, especially at the age of 3 years or below. In Indonesia, it is stated that around 10% of the 430 cases of infant mortality are caused by choking while breastfeeding. Most people don't know what to do when their child chokes, including the babysitter at the TPA Maria Berdukacita Monastery. Caregivers of children have insufficient knowledge in preventing, and recognizing signs of choking and being able to perform first aid for a child who is choking. This condition can be treated by providing information and skills on the Heimlich maneuver technique which is simple, cheap, and applicable to be applied by caregivers in preventing, recognizing, and performing first aid for choking. By providing information and practice, caregivers' knowledge increases regarding the Heimlich maneuver technique in overcoming airway obstruction in children.